Characteristics of Sediment at Littoral Zone of Anoi Itam Beach (Eastern Weh Island, Indonesia) Based on Seasonal Changes - Syahrul Purnawan; Sofyatuddin Karina; Rizka V Ayudia; Yopi Ilhamsyah; Ichsan Setiawan (Graduate Program of Syiah Kuala University, 2020)
Anoi Itam Beach (AIB), located in the eastern part of Weh Island, has the sediment characteristic of dark-sand color. Climatologically, the beach is influenced by two seasons, i.e., south-west (SW) monsoon and northeast (NE) monsoon. Sediment data are collected in the upper and lower littoral zones that are divided into six stations alongshore. Data were collected on October 2016 and April 2017, representing post (SW) monsoon and post-NE monsoon events. To examine the effect of seasonal, sediments statistics, e.g., mean, sorting, skewness, and kurtosis, have been calculated. AIB was characterized as well sorted to poorly sorted sediment. Sediments were identified as mesokurtic in October, varied to leptokurtic and platikurtic in upper littoral and lower littoral, respectively, in April. Grain size in both upper and lower littoral had increased from October to April. The impact on sediment sortation was minor due to the seasonal difference. Sediments in the upper littoral vary slightly skewed than lower littoral, which response to a more positively skewed during seasonal change from SW-monsoon to NE monsoon. The results suggested that lower littoral provide high variability of sediment characteristics depend on the season.